REVIVING AL-KASB: THE ROLE OF TAHFIZ AND PONDOK INSTITUTIONS IN CULTIVATING SOCIAL ENTREPRENEURSHIP - Hamzah, Salman; Abdul Rahim, Mohamad Marzuqi; Adnan, Ahmad Amri Zainal (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
In an era of rising demand for ethical and sustainable economic practices, the Islamic concept of Al-Kasb, which emphasizes lawful and ethical earning, has regained scholarly and practical attention. This mini review investigates the potential of Tahfiz and Pondok institutions, two traditional Islamic educational models, in reviving Al-Kasb through the cultivation of social entrepreneurship. Drawing on interdisciplinary studies, the review explores how these institutions, deeply rooted in spiritual education and community engagement, can evolve into catalysts for value-driven enterprise. The discussion centers on three interrelated themes: social impact, institutional environment, and the integration of social entrepreneurship. Findings suggest that these institutions are uniquely positioned to instil Islamic ethical principles within entrepreneurial ventures aimed at community empowerment and sustainable development. However, challenges persist, including limited financial resources, lack of integration with formal systems, and insufficient context-specific models. The review highlights the need for culturally grounded, Shariah-compliant frameworks tailored to the lived realities of these institutions. This paper contributes to a deeper understanding of how traditional Islamic education can intersect with modern social enterprise, reviving Al-Kasb in ways that are both ethically sound and socially impactful.